Management Disclosures of Going Concern Uncertainties: The Case of Initial Public Offerings - Bochkay, Khrystyna; Chychyla, Roman; Sankaraguruswamy, Srini; Willenborg, Michael (The Accounting Review, 2018)
ABSTRACT We study the information content and determinants associated with voluntary management disclosures of going concern (GC) uncertainties by IPO issuers. In terms of information content, we examine IPO price revision and initial return and find robust support that management GC disclosures are associated with downward revisions in the IPO offer price and, upon considering the mediating effects of the price revision, also associated with lower initial returns. In terms of determinants, and after controlling for other factors (e.g., issuer distress, start-up status, size, cash burn), we find that the presence of a management GC disclosure is negatively associated with a proxy for issuer financial incentives to withhold “bad news” and positively associated with the extent of risk factors disclosure. Overall, our results provide support for the information content of voluntary management disclosures of GC uncertainties by IPO issuers, the presence of which is associated with agency and risk motivations. JEL Classifications: G24; G32; M13; M41.